Hubungan Kadar Vitamin D terhadap Nilai N-Mid Osteocalcin dan C-Terminal Telopeptida di Laboratorium Klinik Prodia Bekasi - Roberto Krisnatalisanto Prabowo Santoso; I Gusti Putu Agus Ferry Sutrisna; Ni Komang Sukra Andini (Universitas Muhammadiyah Manado, 2025)
Vitamin D deficiency can lead to various bone diseases, such as osteoporosis. Standard laboratory tests used to assess bone turnover and formation activity are the N-Mid Osteocalcin (N-Mid) and C-Terminal Telopeptide (C-Tx) tests. Imbalance in N-Mid and C-Tx levels can result in bone health disorders. This study aims to analyze the relationship between Vitamin D levels and N-Mid and C-Tx values. This research used an analytical observational design with a cross-sectional retrospective approach. A total of 32 respondents were selected using total sampling technique. Statistical analysis was performed using Spearman’s Rho test to examine the relationship between Vitamin D levels and N-Mid and C-Tx values. The results showed no significant relationship between Vitamin D levels and N-Mid values (p > 0.05), and no significant relationship between Vitamin D levels and C-Tx values (p > 0.05). The conclusion of this study is that there is no significant relationship between Vitamin D levels and N-Mid Osteocalcin or C-Terminal Telopeptide in patients tested at Laboratorium Klinik Prodia Bekasi. This study provides insights into the importance of monitoring Vitamin D levels in bone disease prevention, even though the results indicate no significant relationship with N-Mid and C-Tx parameters.